Analysis of the studies made in the field of green supply chain management by bibliometric method - Mustafa Deste; Turgay Yıldırım; Aziz Yurttaş (Green Technologies and Sustainability, 2024)
In this study, the studies conducted in the field of “Green Supply Chains” (GSC) between 2010 and 2022 in the Web of Science database were analyzed using the bibliometric method. For this purpose, 1.544 article types of 13 years between the mentioned years were obtained in the “Web of Science” database. The obtained data were analyzed with the R-Studio “biblioshiny” program. In addition, the VOSviewer program was used to visualize the data. With the bibliometric analysis method, the countries with the most publications, the most cited authors, the most cited publications, and the authors with the most publications are shown. In addition to these, the most published journals, the keywords used in the publications, the publication rate by country, the citations received by years and finally the publications made according to the years were examined. As a result of the analysis, it has been understood that the popular and respected position of the “Green Supply Chains” themed studies scanned in the “Web of Science” database has increased more. In addition, it has been determined that the annual number of publications has been increasing in the aforementioned theme, and it has been seen that the authors from different parts of the world have started to publish on a wider range of topics with the joint participation of authors.